Meat consumption and obesity: A climate‐friendly way to reduce health inequalities - Laura Sares‐Jäske; Heli Tapanainen; Liisa Valsta; Peppi Haario; Satu Männistö; Maria Vaalavuo (Public Health Challenges)
Abstract Background Climate change, health inequalities and obesity are considerable public health challenges of the 21st century. Red and processed meat (RPM) consumption is associated with an increased risk of obesity and with higher climate impact. At the same time, educational inequalities exist not only in RPM consumption and obesity but also in other health behaviours. Thus, we investigated whether educational inequalities exist in the association between RPM consumption and obesity, while also considering health behaviours (physical activity, vegetable, legume and fruit consumption, alcohol consumption and smoking) as potential confounding and effect modifying factors. Methods The FinHealth 2017 Study data, including 4494 participants aged 18–74 years, were used. A validated food frequency questionnaire was employed to determine dietary intake. Height and weight were measured by trained study nurses. Linear and logistic regression models were used. Results Odds of obesity increased along with RPM consumption in women (p < 0.001) and men (p < 0.001) and in each educational group regardless of other unfavourable health behaviours. Only in men with basic education were the differences between RPM consumption categories not statistically significant. Compared to those with high education and the lowest RPM consumption, those with basic education and the highest RPM consumption had multiple odds of obesity (odds ratio (95% confidence interval) among women: 7.5 (2.7–20.4); among men: 5.3 (2.5–11.1)). Conclusion High RPM consumption appears to be associated with obesity independently of other unfavourable health behaviours or education, yet the odds are higher with basic education. Targeting unhealthy dietary patterns with heavy ecological burden could help reduce both health inequalities and mitigate climate change.